Incorporation of the ethno-racial approach in the legal and political treatment of climate migrations - San Martín Gómez, Ángela Patricia (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2023)
This article makes a critical analysis of the responses that have been structured at the legal and political levels to address climate migration. It highlights the need to incorporate the ethnic-racial approach in addressing this phenomenon due to its differential impact on the rights of Afro-descendants and indigenous people, especially concerning territory and collective property. It also examines the underlying structural causes and uses this study as a basis for establishing parameters that can be taken into account in the construction of future international policies.